RANCANG BANGUN ALAT UJI KONDUKTIVITAS TERMAL BAHAN - Muhammad Darell Kenundra (2024)
Applications of thermal conductivity are often found in power plants, heating systems, machines and vehicles, to kitchen equipment and other applications. Thermal conductivity is a measure or magnitude of a material's ability to conduct heat (heat). This research aims to determine the design of a material thermal conductivity test tool and obtain the thermal conductivity value of a material. This research uses a variety of materials, namely copper, aluminum, iron and variations in the distance between test points, namely 0.2m and 0.4m. The test object used was in the form of a plate with a length of 60 cm, a width of 4 cm and a thickness of 0.3 cm. The test is carried out with a test object heated with a heating plate and then measuring the temperature at point one and point two at a predetermined distance. The results of testing the copper-0.2m variation showed a thermal conductivity value of 341.9 W/m°C, with an error value of 11.42%. 391.8 W/m°C on a copper variation of -0.4m, with an error value of 6.68%. 195.1 W/m°C on the aluminum-0.2m variation, with an error value of 4.36%. 252.2 W/m°C on the aluminum-0.4m variation, with an error value of 23.63%. 106.3 W/m°C on the Iron-0.2m variation, with an error value of 32.89%. Material thermal conductivity test equipment requires improvements and testing of materials to reduce error values obtained during testing, so that material thermal conductivity test equipment can be used for academic purposes and the results obtained are more precise and optimal.